2008
DOI: 10.1007/s00431-008-0845-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of celiac disease and the diagnostic accuracy of serologic markers in children

Abstract: There has been growing recognition of a changing clinical presentation of celiac disease (CD), with the manifestation of milder symptoms. Serologic testing is widely used to screen patients with suspected CD and populations at risk. The aim of this retrospective analysis was to evaluate the clinical presentation of CD in childhood, assess the diagnostic value of serologic tests, and investigate the impact of IgA deficiency on diagnostic accuracy. We evaluated 206 consecutive children with suspected CD on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 31 publications
7
22
0
1
Order By: Relevance
“…On the other hand, some studies have reported that diarhhea has been observed with a lower frequency in recent years (25,26). Similarly, gastrointestinal symptoms including abdominal distension, weight loss, constipation, vomiting and abdominal pain have been reported to gradually decrease in recent years (12,20,27). In accordance with the literature, we found these gastrointestinal sypmtoms with a lower rate in our celiac group compared to the control group.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, some studies have reported that diarhhea has been observed with a lower frequency in recent years (25,26). Similarly, gastrointestinal symptoms including abdominal distension, weight loss, constipation, vomiting and abdominal pain have been reported to gradually decrease in recent years (12,20,27). In accordance with the literature, we found these gastrointestinal sypmtoms with a lower rate in our celiac group compared to the control group.…”
Section: Discussionsupporting
confidence: 90%
“…Further inquiries into the medical records of these infants indicated that the presenting clinical symptoms did not differ significantly from those of biopsy-proven celiac children (10). In the majority of cases (64%), the clinical symptoms persisted throughout the follow-up period.…”
mentioning
confidence: 82%
“…Celiac disease (CD), also known as gluten-sensitive entheropathy or celiac sprue, is a multifactorial inflammatory small bowel disorder characterized by malabsorbtion that is triggered by mucosal damage, the latter occuring, as a response to gliadin fraction of gluten found in cereal products like barley, oat, rye, and wheat (Bracken et al, 2008;Lurz et al, 2009). Nowadays, it is known that CD is an illness that involves all body systems alongside the typical enteropathy and is more complicated than simple malabsorption (Ertekin et el., 2005;Hill et al, 2005;Mehta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that immunological and genetic factors, and gluten as an environmental factor all play important roles in etiopathogenesis of CD (Ertekin et al, 2005;Demirceken et al, 2008). Commonly observed clinical symptoms in CD are diarrhea, vomiting, abdominal pain, weight loss, general weakness, muscle wasting, loss of appetite, growth and developmental retardation, and bad smelling, fatty stool (Lurz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%